2014
DOI: 10.3390/ijms150712807
|View full text |Cite
|
Sign up to set email alerts
|

Modified Low Density Lipoprotein and Lipoprotein-Containing Circulating Immune Complexes as Diagnostic and Prognostic Biomarkers of Atherosclerosis and Type 1 Diabetes Macrovascular Disease

Abstract: In atherosclerosis; blood low-density lipoproteins (LDL) are subjected to multiple enzymatic and non-enzymatic modifications that increase their atherogenicity and induce immunogenicity. Modified LDL are capable of inducing vascular inflammation through activation of innate immunity; thus, contributing to the progression of atherogenesis. The immunogenicity of modified LDL results in induction of self-antibodies specific to a certain type of modified LDL. The antibodies react with modified LDL forming circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 215 publications
(265 reference statements)
1
53
0
4
Order By: Relevance
“…Elevated levels of CICs of glycoxidized LDL has been reported to be associated with retinopathy in type 1 diabetes and in the pathogenesis of atherosclerosis (6,12). In fact, modified LDL associated with the immune complexes are proinflammatory, atherogenic and accumulating evidence indicates that LDL-containing immune complexes can also serve as a biomarker for macrovascular disease in type 1 diabetes (13). Further, it is reported that a major percentage of antibodies against AGE-modified proteins were constituted by IgGs in the diabetic patients (14).…”
Section: Formation Of Advanced Glycation End Products (Ages)mentioning
confidence: 99%
“…Elevated levels of CICs of glycoxidized LDL has been reported to be associated with retinopathy in type 1 diabetes and in the pathogenesis of atherosclerosis (6,12). In fact, modified LDL associated with the immune complexes are proinflammatory, atherogenic and accumulating evidence indicates that LDL-containing immune complexes can also serve as a biomarker for macrovascular disease in type 1 diabetes (13). Further, it is reported that a major percentage of antibodies against AGE-modified proteins were constituted by IgGs in the diabetic patients (14).…”
Section: Formation Of Advanced Glycation End Products (Ages)mentioning
confidence: 99%
“…ЛПВП обладают не-сколькими видами противовоспалительной активности, включая ингибирование индуцированной цитокинами экспрессии моле-кул адгезии на эндотелиальных клетках (ЭК), ингибирование ад-гезии моноцитов к эндотелию, подавление активации моноцитов путем ингибирования синтеза провоспалительных цитокинов и хемокинов, снижение активации нейтрофилов и торможение ин-фильтрации нейтрофилов в стенке артерии [44][45][46]. Противовос-палительная активность ЛПВП по отношению к ЭК и моноцитам может быть связана с извлечением липидов из этих клеток по-средством ABCA1 и ABCG1 [46].…”
Section: терапевтический архив 9 2016unclassified
“…[14,84] In 2013 Montano [85] and colleagues showed that monoclonal anti-oxLDL IgM (E06) inhibited oxLDL binding to macrophages in a dose dependent manner. Studies on LDL-CIC discovered that LDL in these complexes had atherogenic modifications, particularly LDL were small dense and had decreased sialic acid content.…”
Section: [80]mentioning
confidence: 99%
“…[11,12] During the past decades, numerous studies confirmed that LDL modifications, such as oxidation, desialylation and enzymatic processing, play a key role in increasing cholesterol intake, and the level of multiple modified LDL correlates with the risk of CVD. [13,14] Other types of lipoproteins that are distinguished in some studies are electronegative LDL [LDL(-)] and lipoprotein (a) [Lp(a)]. The former subclass includes modified LDL with increased negative charge, which accounts for 3-5% of the total LDL in normolipidemic subjects.…”
Section: Modified Ldl and Atherosclerosismentioning
confidence: 99%